Increased Expression of Secreted Frizzled-Related Protein 4 in Polycystic Kidneys - Romaker, Daniel; Puetz, Michael; Teschner, Sven; Donauer, Johannes; Geyer, Marcel; Gerke, Peter; Rumberger, Brigitta; Dworniczak, Bernd; Pennekamp, Petra; Buchholz, Björn; Neumann, H. P. H.; Kumar, Rajiv; et al. (Journal of the American Society of Nephrology, 2009)
Autosomal dominant polycystic kidney disease (ADPKD) is a common hereditary disease associated with progressive renal failure. Although cyst growth and compression of surrounding tissue may account for some loss of renal tissue, the other factors contributing to the progressive renal failure in patients with ADPKD are incompletely understood. Here, we report that secreted frizzled-related protein 4 (sFRP4) is upregulated in human ADPKD and in four different animal models of PKD, suggesting that sFRP4 expression is triggered by a common mechanism that underlies cyst formation. Cyst fluid from ADPKD kidneys activated the sFRP4 promoter and induced production of sFRP4 protein in renal tubular epithelial cell lines. Antagonism of the vasopressin 2 receptor blocked both promoter activity and tubular sFRP4 expression. In addition, sFRP4 selectively influenced members of the canonical Writ signaling cascade and promoted cystogenesis of the zebrafish pronephros. sFRP4 was detected in the urine of both patients and animals with PKD, suggesting that sFRP4 may be a potential biomarker for monitoring the progression of ADPKD. Taken together, these observations suggest a potential role for SFRP4 in the pathogenesis of ADPKD.